The Role Of Parental Involvement In The Education Process Of Children In High School - Sitompul, Adelia; Pardede, Sanggam; Siahaan, Nova Yunita Sari (Jurnal Pendidikan, Sains Sosial, dan Agama, 2023)
The phenomenon of low parental involvement in children’s education is still evident at HKBP Sidorame Private Senior High School Medan, such as limited participation in school activities and communication with teachers, which affects both academic support and character development of students. This study aims to examine the role of parental involvement in the educational process using a qualitative approach with a case study method, involving parents, teachers, and students through interviews, observations, and documentation. The findings show that parental involvement plays an important role in students’ learning success, through home guidance, communication with the school, and participation in school activities, yet the level of involvement varies due to factors such as occupation, time availability, and awareness of education. The greater the parental involvement, the more positive the impact on the educational process of students at school